Strategies to Improve the Efficacy of Dendritic Cell-Based Immunotherapy for Melanoma - Hargadon, Kristian M. (Frontiers in Immunology, 2017)
Melanoma is a highly aggressive form of skin cancer that frequently metastasizes to vital organs, where it is often difficult to treat with traditional therapies such as surgery and radiation. In such cases of metastatic disease, immunotherapy has emerged in recent years as an exciting treatment option for melanoma patients. Despite unprecedented successes with immune therapy in the clinic, many patients still experience disease relapse, and others fail to respond at all, thus highlighting the need to better understand factors that influence the efficacy of anti-tumor immune responses. At the heart of anti-tumor immunity are dendritic cells, an innate population of cells that function as critical regulators of immune tolerance and activation. As such, dendritic cells have the potential to serve as important targets and delivery agents of cancer immunotherapies. Even immunotherapies that do not directly target or employ dendritic cells, such as checkpoint blockade therapy and adoptive cell transfer therapy, are likely to rely on dendritic cells that shape the quality of therapy-associated anti-tumor immunity. Therefore, understanding factors that regulate the function of tumor-associated dendritic cells is critical for optimizing both current and future immunotherapeutic strategies for treating melanoma. To this end, this review focuses on advances in our understanding of dendritic cell function in the context of melanoma, with particular emphasis on 1) the role of immunogenic cell death in eliciting tumor-associated dendritic cell activation, 2) immunosuppression of dendritic cell function by melanoma-associated factors in the tumor microenvironment, 3) metabolic constraints on the activation of tumor-associated dendritic cells, and 4) the role of the microbiome in shaping the immunogenicity of dendritic cells and the overall quality of anti-melanoma immune responses they mediate. Additionally, this review highlights novel dendritic cell-based immunotherapies for melanoma that are emerging from recent progress in each of these areas of investigation, and it discusses current issues and questions that will need to be addressed in future studies aimed at optimizing the function of melanoma-associated dendritic cells and the anti-tumor immune responses they direct against this cancer.